Super foods cookbook : 184 easy recipes to boost your health (Readers Digest, 2014)
"Eat your way to optimum health with 184 recipes that pack a nutritional punch. Each recipe contains at least one superfood designed to boost energy, promote health and well-being, and protect against disease. Discover the exceptional nutritional content and disease-fighting qualities of super foods like broccoli, blueberries, and salmon and delicious, healthful ways to prepare them. By including super foods as part of a balanced diet, you can protect your heart, immune system, digestive system, skin, and bones, and even reduce the risk of developing certain medical conditions later in life. In Super Foods Cookbook you'll find 184 health-boosting recipes, all of which include at least one super food. Each recipe offers clear step-by-step cooking instructions, ingredient information, and invaluable tips. These recipes and foods are proven to prevent, fight, and beat problems big and small. The Super Foods Benefits Chart lists the foods best suited to heal what ails you, from fatigue and depression to osteoporosis and arthritis, as well as their positive benefits to the body"--